2010
DOI: 10.1107/s1600536810014571
|View full text |Cite
|
Sign up to set email alerts
|

N-(2,6-Dimethylphenyl)-4-methylbenzenesulfonamide

Abstract: In the title compound, C15H17NO2S, the mol­ecule is bent at the S atom, the C—SO2—NH—C torsion angle being 88.0 (2)°. The dihedral angle between the two aromatic rings is 49.8 (1)°. In the crystal, mol­ecules are linked into zigzag chains parallel to the a axis via N—H⋯O hydrogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Interestingly, it was observed that the N -sulphonylation of urazoles proceeds in high yields and only mono-sulphonylated products were produced (table 1, entries [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, it was observed that the N -sulphonylation of urazoles proceeds in high yields and only mono-sulphonylated products were produced (table 1, entries [16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…The products were characterized on the basis of their spectral (IR, NMR) and melting points and compared with literature. 7,[14][15][16][17][18][19][20][21] Formation of expected sulphonamides is evidenced by disappearance of single and strong absorption band for N-H stretching bond and appearance of two stretching bands for SO 2 group in their IR spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation